2024
DOI: 10.1088/1748-9326/ad1ad0
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between the water-energy-food nexus and compound risks

J Leah Jones-Crank,
Jessie Lu,
Ben Orlove

Abstract: The water-energy-food (WEF) nexus is a concept and approach to examine the interactions of water, energy, and food resources. Similarly, compound risks are a set of risk types that consider multiple connected factors that amplify risks. While both concepts are promoted as approaches to move beyond silos and address complex problems in environmental governance, there has been limited exploration of their overlap. Our study integrates these two approaches for more holistic assessment and management of resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The integration of Focus Maps into environmental management, particularly within the context of the WEF Nexus, is a pivotal advancement in understanding and addressing the complex interdependencies between natural and human systems. The concept of the WEF Nexus, which underscores the intricate connections between water, energy, and food systems, is crucial for sustainable development and requires a comprehensive and integrated management approach [6,7]. By converting complex data into an accessible format, these maps enable informed decision-making and facilitate a deeper understanding of the Nexus [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of Focus Maps into environmental management, particularly within the context of the WEF Nexus, is a pivotal advancement in understanding and addressing the complex interdependencies between natural and human systems. The concept of the WEF Nexus, which underscores the intricate connections between water, energy, and food systems, is crucial for sustainable development and requires a comprehensive and integrated management approach [6,7]. By converting complex data into an accessible format, these maps enable informed decision-making and facilitate a deeper understanding of the Nexus [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The water-energy-food (WEF) nexus represents a concept to describe and address, to better understand and systematically analyze the interactions between the natural environment and human activities [1]. This concept, which underscores the intricate connections between water, energy, and food systems, is crucial for sustainable development and requires a comprehensive and integrated management approach [2,3]. Harwood (2018) called for a ''systems thinking" approach that can help effectively evaluate and implement actions in regard to the area pertaining to the WEF nexus [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Tulcea WEF nexus, a case study of a mid-sized city in the Danube Delta (Tulcea, population size: 65.624; population density: 571 inhabitants per km 2 ; census, 2021), was explored in two prior studies [20,21]. The key finding pertinent to this study was that the WEF nexus showed less awareness among local residents in Tulcea than could be expected from rural development, as analyzed by scientists (for degradation of environment see, e.g., [22]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation